SWOT Analysis Of The PLN Mobile Application For Customers Of PT PLN UP3 Merauke - Nur Annisa Triswati; Alldila Nadhira Ayu Setyaning (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) of the PLN Mobile application to improve customer interaction and maximize the use of digital transactions at PT PLN UP3 Merauke. The main problems faced are the lack of digital socialization and education and limited internet network and infrastructure constraints in the Merauke area that hinder access and use of the application. The research method used is qualitative with data collection through observation and interviews related to application usage and marketing strategies. The results show that the PLN Mobile application has advantages such as ease of use, low admin costs, and fast response, but faces challenges in irrelevant features and dependence on a stable network. Opportunities for increasing application usage are supported by collaboration with MSMEs, broader digital education, and strengthening customer service. The strategy of strengthening the application through feature innovation and digital education can increase customer interaction and awareness of digital services. This study recommends increasing socialization and improving application features tailored to user characteristics to strengthen PLN Mobile's position as a trusted and inclusive digital electricity service platform.